Ocorrência de Meloidogyne enterolobii em muricizeiro (Byrsonima cydoniifolia) - Paes, Vanessa dos S. [UNESP]; Soares, Pedro L.M. [UNESP]; Murakami, Devanir M.; Santos, Jaime M. dos [UNESP]; Barbosa, Bruno F.F. [UNESP]; Neves, Samira S. [UNESP] (Sociedade Brasileira de Fitopatologia, 2012)
A entrada de agentes fitopatogênicos em novas localidades através de mudas infectadas constitui uma das principais formas de disseminação. Meloidogyne enterolobii é uma espécie de nematoide altamente virulenta que tem causado sérios danos a plantas cultivadas no Brasil. Neste trabalho é relatada a primeira ocorrência de M. enterolobii em mudas de muricizeiro (Byrsonima cydoniifolia), uma planta nativa da Amazônia e em mudas de goiabeira (Psidium guajava), no Estado de Mato Grosso. Com base nos caracteres morfológicos do padrão perineal de fêmeas, região labial dos machos e no fenótipo isoenzimático de esterase, foi confirmado que a espécie encontrada tanto nas mudas de muricizeiro quanto nas de goiabeira é M. enterolobii.

Spreading of plant pathogens through seedlings is one of the main ways of introducing pathogens in places free of these agents. Meloidogyne enterolobii is a highly virulent species of nematode responsible for serious damage to plants grown in Brazil. In this study the occurrence of M. enterolobii on young individuals of muricizeiro (Byrsonima cydoniifolia), a native species of the Amazon forest, is made for the first time together with the first report of the occurrence of this nematode on guava (Psidium guajava) in the State of Mato Grosso, Brazil. Based on morphological characters of the perineal pattern of females, lip region of males and the esterase isoenzyme phenotype, we confirmed that the species found in both of B. cydoniifolia and P. guajava is M. enterolobii.
Occurrence of Meloidogyne enterolobii on muricizeiro of (Byrsonima cydoniifolia)
Keywords: Psidium guajava; Cerrado; goiabeira; nematoide de galha; Psidium guajava; Brazilian savannah; guava; root knot nematode